SMART CARD PROGRAM EFFECTIVENESS IN AN EFFORT TO REDUCE THE SCHOOL DROPOUT RATE IN SUKABUMI CITY - Gunawan, Maghfira Maulida; Meigawati, Dine; Mulyadi, Andi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to determine the implementation of the Smart Card program carried out by the Sukabumi City Education and Culture Office. This research uses qualitative research methods with a case study approach consisting of 5 informants who are divided into two groups of program implementer informants and target program implementer informants, data collection techniques using observation, interviews, and documentation techniques, then data analysis using a flow model, and data validation using source triangulation and technical triangulation. This research uses Duncan's theory of effectiveness in Steers (53: 1985). The results of this study indicate that the implementation of the Smart Card program is right on target, because it is in accordance with the original objectives made, namely for students who are lacking in economic terms and are not registered as KIP recipients. Achieving this goal makes students who experience economic limitations still able to go to school because getting an education is a right in accordance with the 1945 basic law. The integrity of this Smart Card program is where the Sukabumi City Education and Culture Office is optimal in conducting socialization to junior high schools in Sukabumi City and then the school also conducts socialization to student guardians and students who are the target of the smart card program, and the communication process from the school to the Sukabumi City local government is well established so that it can implement this program every year. In the process of planning this smart card, where the identification to the implementation of the distribution of Smart Cards is in accordance with the objectives and implementation and technical guidelines of the program.